Cooperation of lactic acid bacteria regulated by the AI-2/LuxS system involve in the biopreservation of refrigerated shrimp. (June 2019) - Li, Jianpeng; Yang, Xiaoyuan; Shi, Guocui; Chang, Jing; Liu, Zunying; Zeng, Mingyong
Abstract: Litopenaeus vannamei is an extremely perishable food because of rapid microbial growth and chemical degradation after harvesting. Biopreservation is a food preservation technology based on the addition of "positive" bacteria to kill or prevent the growth of undesirable microorganisms. In this study, the cooperation between lactic acid bacteria (LAB) strains ( Lactobacillus plantarum AB-1 and Lactobacillus casei ) regulated by the AI-2/LuxS was investigated in vitro and on shrimp. The antimicrobial activity of L. plantarum AB-1 was significantly increased in the co-culture compared with the mono-culture in vitro, and the transcription of the quorum sensing luxS gene and bacteriocin regulatory operons ( plnB and plnC ) in L. plantarum AB-1 were also significantly increased in co-culture ( P  < .05), indicating cooperation and that the production of bacteriocin in L. plantarum AB-1 might be related to the LuxS/AI-2 quorum sensing (QS) system. The results were confirmed by adding the exogenous AI-2 molecule signal to L. plantarum AB-1 in vitro . In the on shrimp experiments, the spoilage organisms (mainly Shewanella baltica ) in shrimp samples were significantly inhibited after co-inoculation with L. plantarum AB-1 and L. casei, and the values of total volatile basic nitrogen (TVB-N) and pH in co-inoculated shrimp were also significantly decreased ( P  < .05). In addition, the AI-2 activities in co-inoculated shrimp were significantly higher during refrigerated storage. The results suggest that the cooperation and bacteriocin production of lactic acid bacteria might by regulated by the AI-2/LuxS system, and the co-inoculation of L. plantarum AB-1 and L. casei in shrimp is an effective strategy for biopreservation of shrimp. Graphical abstract: Unlabelled Image Highlights: Antimicrobial activity of lactic acid bacteria significantly increased in co-culture. Bacteriocin production in lactic acid bacteria is related to the LuxS/AI-2 system. Co-inoculation of lactic acid bacteria has better preservation effect. Quorum sensing system LuxS/AI-2 involves in biopreservation of lactic acid bacteria.